Upaya Peningkatan Hasil Belajar Tematik Melalui Model Pembelajaran Numbered Heads Together - Sri Rezeki HB (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine whether there is an increase in the learning outcomes of third grade students at SD Negeri 47 Lubuklinggau on the theme of 3 objects around me using the Numbered Heads Together (NHT) learning model. This research uses Classroom Action Research (CAR) for two cycles. The results showed that the data obtained in the first cycle the average value of the evaluation of the 3 objects around me was 74.44 with a learning mastery percentage of 74% and in the second cycle the average student evaluation score was 82.96 with a learning completeness percentage of 85%. , it is seen that each learning cycle there is an increase. In the first cycle the results of student activity observations were 72.04 with a percentage of 72% in the active category, and in the second cycle it increased again to 81.85 with a percentage of 82% in the very active category. In conclusion, the Numbered Heads Together (NHT) learning model can improve the learning outcomes of third grade students at SD Negeri 47 Lubuklinggau on the theme of 3 objects around me. Keywords: Learning Outcomes, Numbered Heads Together, Tematik